What has Capital Liberalization Meant for Economic and Financial Statistics - Heath, Robert (IMF Working Papers; Working Paper ;, 2015)
The liberalization of capital flows both in the domestic economy and cross-border has been among the most important policies adopted by IMF member countries over recent decades. The impact has been wide-ranging. This paper looks at the impact on the field of economic and financial statistics in the past two decades, as statisticians have responded to the changing policy needs. The paper considers the historical context of changes that have occurred, draws out the key trends, and asks where these trends might lead statisticians in the foreseeable future. The paper considers that there has been nothing short of a revolution in the field of economic and financial statistics over the past two decades led by a need for greater transparency; greater standardization; new data sets to support understanding of financial interconnections and financial sector risks; and the strengthening of the governance of the statistical function through greater independence of statistical agencies.